Effect of agroindustrial wastes on the mycelium growth of Pleurotus sp. "Florida", in Uberlândia, Brazil - Zanetti, Ana Luísa; Ranal, Marli A. (Pesquisa Agropecuaria Brasileira, 1996)
The effect of different agroindustrial wastes in the region of Uberlândia, MG, Brazil, on the mycelium growth of Pleurotus sp. "Florida" was studied. The experiment was conducted from June 26 to July 30, 1993. The average minimum and maximum temperatures registered were 21.4 and 25.1°C, respectively. The substrates used were agroindustrial wastes of cotton (Gossypium sp.), guariroba (Syagrus oleracea), maize (Zea sp.), soybean (Glycine sp.), and triturated sugar cane (Saccharum sp.). The parameters studied were the average mycelium growth time and speed. The minor average mycelium growth time was registered in the cotton and guariroba residues (ca. ten days). The cotton and guariroba residues, as well as tritured sugar cane were the most favorable substrates for the increase in the mycelium growth speed. The colonization efficiency of the mycelium in these residues indicates their viability for conversion in food (fruit bodies).
Keywords: colonization efficiency; edible mushroom; cultivation